Mouse model for Pneumocystis carinii pneumonia that uses natural transmission to initiate infection. - Powles, M A (1992)
Animal models for Pneumocystis carinii, for the most part, have been limited to immunosuppressed rats and ferrets, while a dependable mouse model has been more difficult to develop. A P. carinii mouse model has now been established with several strains of mice, including C3Heb/FeJ, C3HeN, BALB/c, DBA/2N, and BALB/c nu/nu (athymic). In lieu of using invasive methods for initiating P. carinii infections, mice harboring P. carinii transmitted the disease to mice without latent infection via short-term cohabitation. After the exposure period, the seed mice were sacrificed to confirm the presence of acute P. carinii pneumonia. Acute infections in recipient mice developed at approximately 7 to 8 weeks, while control unseeded littermates remained uninfected. All recipient mice and their littermates were maintained in isolation hoods to eliminate the possibility of exposure to other sources of P. carinii. This approach allows investigators to consistently transmit P. carinii to mice and to select the strain of mouse desired for use in a particular study. The results presented here suggest that more attention should be given to the potential for patient-to-patient transmission of P. carinii in immunocompromised patients such as those with AIDS.